2009
DOI: 10.1016/j.tripleo.2009.02.023
|View full text |Cite
|
Sign up to set email alerts
|

Research diagnostic criteria for temporomandibular disorders (RDC/TMD): development of image analysis criteria and examiner reliability for image analysis

Abstract: Introduction As a part of a multi-site RDC/TMD Validation Project, comprehensive TMJ diagnostic criteria were developed for image analysis using panoramic radiography, magnetic resonance imaging (MRI), and computed tomography (CT). Methods Inter-examiner reliability was estimated using the kappa (k) statistic, and agreement between rater pairs was characterized by overall, positive, and negative percent agreement. CT was the reference standard for assessing validity of other imaging modalities for detecting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
561
9
39

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 557 publications
(618 citation statements)
references
References 75 publications
9
561
9
39
Order By: Relevance
“…The disc position classified into normal when anterior border of the disc located superior to the condyle, anteriorly displaced when the anterior border of the disc presents anterior to the condyle, medially displaced when the disc boundary shifted medial to boundary of the condyle, laterally displaced when the disc boundary shifted lateral in comparison to the boundary of the condyle. On MR imaging, the normal and displaced disc position categorized according to previous criteria [30].…”
Section: Methodsmentioning
confidence: 99%
“…The disc position classified into normal when anterior border of the disc located superior to the condyle, anteriorly displaced when the anterior border of the disc presents anterior to the condyle, medially displaced when the disc boundary shifted medial to boundary of the condyle, laterally displaced when the disc boundary shifted lateral in comparison to the boundary of the condyle. On MR imaging, the normal and displaced disc position categorized according to previous criteria [30].…”
Section: Methodsmentioning
confidence: 99%
“…[2][3][4] Another paper reports the 95z accuracy of MR imaging in assessing disk position and form and 93z accuracy in assessing osseous changes. 5 Proton density-weighted images (PDWI) are necessary to detect the position and deformity of the articular disk, [6][7][8] and T 2 -weighted images (T 2 WI) are necessary to detect the level of joint eŠusion, which is associated with pain. 8,9 A dual echo technique is generally used for 2-dimensional (2D)-PDWI and -T 2 WI scans.…”
Section: Introductionmentioning
confidence: 99%
“…8 The results showed that 1 of the 14 patients (7% of TMJs) had osteoarthritis at the 6-year follow-up and 3 of the 14 patients (18% of TMJs) at the 32-year follow-up. These results are in line with the frequencies of osteoarthritis found in a recent CBCT study on subjects without ongoing pain.…”
Section: Discussionmentioning
confidence: 96%
“…The TMJs (condylar head, mandibular fossa, and articular eminence) were interpreted for structural bone changes. The diagnosis of osteoarthritis was made according to Ahmad et al 8 ( Table 2). The interpretations of the radiographs were made by one observer (AP) at T3 6 and by two observers (Dr Petersson and Dr Salé ) at T4.…”
Section: Tmj Radiographymentioning
confidence: 99%